Brincadeira apressada: uma reflexão sobre o tempo de brincar nos anos iniciais - Campos, Júlia Novaes de Araújo (Universidade Federal de São Carlos, 2024)
This study investigates the presence of and respect for playtime and spaces for children in the Early Years of Elementary School within the school environment. The study explores the following question: have children been respected in their right to choose when and where to play at school? In response to this question, other relevant issues are addressed, such as the importance of play for children's development and learning, the free time available in the school routine, and the existence of adequate spaces for play, both indoors and outdoors. The objectives were to analyze the relevance of free play for children and to evaluate the adequacy of educational practices regarding its promotion. The research has a qualitative approach, characterized as bibliographic and includes an experience report. The literature review sought references on the concept of play, the distinction between free and guided play, and the investigation of the times and spaces available for play in schools. The writing of an experience report aimed to reflect on children's right to play, examining the presence and quality of play opportunities offered at school.
Playing in a hurry: a reflection on playtime in the elementary school
Keywords: Brincar; Play; Jogo e brincadeira; Games and play; Ensino fundamental; Elementary school; Anos iniciais; Early years; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO